Analysis Of The Application Of Liability Accounting As A Measure Of Profit Center Manager Achievement At LUMBA – LUMBA - Dyatri Utami; Arina Absari (CV. AFDIFAL MAJU BERKAH, 2022)
The aims of this research are 1). How is the implementation and application of the profit center responsibility accounting system at Lumba-Lumba. 2).Is the accountability accounting at Lumba-Lumba adequate. 3). How is the influence of responsibility accounting as a measure of the achievement of profit center managers. This research is classified as a case study, namely the type of research used to find out the problems that occur in the company objectively and analyze and solve problems using theories that are related to the topics discussed. The location chosen is LUMBA-LUMBA Turen Malang From the research results can draw conclusions as follows 1). The organizational structure at Lumba-Lumba is basically still simple and in certain parts there is still no clear separation of duties or duplication of duties. 2). In the preparation of the budget, it has not been recorded so that the budget cannot be used as a control tool in the event of deviations between the budget and its realization. 3). Classification of costs and the imposition of an account code that does not yet exist causes costs to not be classified into controllable costs and uncontrollable costs. 4). There is no manager's performance appraisal of work results. 5). The financial reporting system is still very simple.